Topography of genetic loci in tissue samples: towards new diagnostic tool using interphase FISH and high-resolution image analysis techniques - Koutná, I; Kozubek, S; Zaloudík, J; Kozubek, M; Lukásová, E; Matula, P; Bártová, E; Skalníková, M; Cafourková, A; Jirsová, P (Analytical cellular pathology, 2000)
Using single and dual colour fluorescence in situ hybridisation (FISH) combined with image analysis techniques the topographic characteristics of genes and centromeres in nuclei of human colon tissue cells were investigated. The distributions of distances from the centre-of-nucleus to genes (centromeres) and from genes to genes (centromeres to centromeres) were studied in normal colon tissue cells found in the neighbourhood of tumour samples, in tumour cell line HT-29 and in promyelocytic HL-60 cell line for comparison. Our results show that the topography of genetic loci determined in 3D-fixed cell tissue corresponds to that obtained for 2D-fixed cells separated from the tissue. The distributions of the centre-of-nucleus to gene (centromere) distances and gene to gene (centromere to centromere) distances and their average values are different for various genetic loci but similar for normal colon tissue cells, HT-29 colon tumour cell line and HL-60 promyelocytic cell line. It suggests that the arrangement of genetic loci in cell nucleus is conserved in different types of human cells. The investigations of trisomic loci in HT-29 cells revealed that the location of the third genetic element is not different from the location of two homologues in diploid cells. We have shown that the topographic parameters used in our experiments for different genetic elements are not tissue or tumour specific. In order to validate high-resolution cytometry for oncology, further investigations should include more precise parameters reflecting the state of chromatin in the neighbourhood of critical oncogenes or tumour suppresser genes.
Keywords: DNA, Neoplasm; buněčné jádro; hybridizace in situ fluorescenční; počítačové zpracování obrazu; HT29 Cells; Interphase; In Situ Hybridization, Fluorescence; nádory tračníku; interfáze; Cell Nucleus; Centromere; Humans; centromera; Colonic Neoplasms; DNA nádorová; Image Processing, Computer-Assisted; HL-60 buňky; buňky HT-29; lidé; HL-60 Cells